Analisis penggunaan afiksasi pada lirik lagu “Everything U Are” karya Baskara Putra - Mauliddina, Rofi’atul (Maliki Interdisciplinary Journal, 2025)
This research discusses the use of affixation found in the lyrics of Everything U Are by Baskara Putra or often called Hindia. Affixation is the process of forming new words in a language by adding affixes to the base word. There are several types of affixes which can be prefixes, suffixes, infixes, or a combination of prefixes and suffixes. This song was chosen because it is billingual although only two verses are in English, so there are variations in the use of affixes from both languages and this song is one of the most popular songs on the album, so researchers are interested in studying this song. This research uses descriptive qualitative method by analyzing affixed words in song lyrics. The data is obtained from the song lyrics which are then analyzed to identify the types of affixation used, such as prefixes, suffixes, and confixes. The results show that the number of each type of affix analyzed and found are prefixes totaling 10 data, suffixes totaling 16 data, and confixes totaling 7 data. With a total of 33 data. The number of affixation findings shows that the process of word formation through affixes plays an important role in shaping the structure and meaning of song lyrics. Besides playing an important role in shaping structure and meaning, the use of affixes in song lyrics also gives an emotional and poetic feel so that the message to be conveyed becomes stronger.